Green building materials lit up by electromagnetic absorption function: A review - Liu, Ting-Ting; Cao, Mao-Qing; Fang, Yong-Sheng; Zhu, Yu-Hang; Cao, Mao-Sheng (Journal of materials science & technology, 2022)
•The progress in building electromagnetic waves absorbing materials is reviewed.•We classify electromagnetic waves absorbing materials from building angles.•The challenges of building electromagnetic waves absorbing materials are analyzed.•The future research direction is analyzed systematically and comprehensively. Healthy and livable living environments, as well as anti-electromagnetic (EM) radiation buildings, are the long-term goals of human beings. The introduction of advanced EM wave absorbing materials into buildings is one of the most feasible ways to address the increasing EM pollution in building spaces. High-efficiency, broadband, low-cost and good building performance EM wave absorbing materials, as an important support in the field of sustainable building, has gradually become the hotspot research. Here, we review the research progress of building materials with EM wave absorption functions, and comb their classification, including cement, concrete, ceramics, and prefabs, especially highlighting the advanced coating materials. We objectively outline and evaluate the latest technology of building materials with EM wave absorption performance, and discuss the main problems and bottlenecks, highlighting potential research opportunities.